Efektivitas Penggunaan Tiktok Ads Terhadap Peningkatan Jumlah Pengunjung pada Eduwisata Aloeland di PT. Mount Vera Sejati (Jurnal Riset Manajemen dan Akuntansi, 2025)
The development of digital technology, particularly the use of social media like Tiktok, had transformed the marketing paradigm for companies across various sectors. Eduwisata Aloeland, managed by PT Mount Vera Sejati, utilized Tiktok ads to enhance visibility and attract more visitors to its educational tourism destination. This study aimed to evaluate the effectiveness of Tiktok ads by focusing on three main aspects: audience interaction, account growth, and promotional efficiency through Revenue Cost Ratio (R/C Ratio) analysis. A quantitative approach was applied using data obtained from Tiktok analytics to provide accurate and measurable results. The findings showed significant improvements across all measured parameters. Audience interaction increased by an average of 98.04%, indicating higher engagement with the promoted content. Account growth also showed a substantial increase of 69.40%, demonstrating success in expanding audience reach. Additionally, the R/C Ratio calculation for Tiktok ads promotions reached 1.35, meaning that for every Rp1.00 spent on promotion, Rp1.35 in revenue was generated. The study concluded that Tiktok ads was a highly effective digital marketing strategy for increasing visibility and attracting more visitors to Eduwisata Aloeland. By using social media like Tiktok, Eduwisata Aloeland successfully attracted a broader and more relevant audience, enhancing its presence in the digital world.